Regional innovation networks from two perspectives – innovation as an essence of local development (The Case of Slovak region) - Prochádzková, Martina (Észak-magyarországi Stratégiai Füzetek, 2013)
Diversity of human knowledge which can be considered as a precondition of technological change leads to more or less economic development. The role of space could not be ignored and it is necessary to understand why networks of innovative actors can have a local dimension which is stronger or weaker in the sense of economic geography and economics of knowledge. The paper uses social network analysis to create networks of innovative actors – one for innovators and one for inventors. The main aim of applying mentioned concepts is to recognize actors that can be considered as carriers of knowledge and to identify differences among them. Calculated characteristics of networks suggest that in the case of Košice region, the bulk of knowledge can be found on the inventor´s side.